Differences in the intrinsic chondrogenic potential of human mesenchymal stromal cells and iPSC‐derived multipotent cells. Issue 12 (19th December 2022) - Xiang, Shiqi; Lin, Zixuan; Makarcyzk, Meagan J.; Riewruja, Kanyakorn; Zhang, Yiqian; Zhang, Xiurui; Li, Zhong; Clark, Karen L.; Li, Eileen; Liu, Silvia; Hao, Tingjun; Fritch, Madalyn R.; et al.
Abstract: Background: Human multipotent progenitor cells (hiMPCs) created from induced pluripotent stem cells (iPSCs) represent a new cell source for cartilage regeneration. In most studies, bone morphogenetic proteins (BMPs) are needed to enhance transforming growth factor‐β (TGFβ)‐induced hiMPC chondrogenesis. In contrast, TGFβ alone is sufficient to result in robust chondrogenesis of human primary mesenchymal stromal cells (hMSCs). Currently, the mechanism underlying this difference between hiMPCs and hMSCs has not been fully understood. Methods: In this study, we first tested different growth factors alone or in combination in stimulating hiMPC chondrogenesis, with a special focus on chondrocytic hypertrophy. The reparative capacity of hiMPCs‐derived cartilage was assessed in an osteochondral defect model created in rats. hMSCs isolated from bone marrow were included in all studies as the control. Lastly, a mechanistic study was conducted to understand why hiMPCs and hMSCs behave differently in responding to TGFβ. Results: Chondrogenic medium supplemented with TGFβ3 and BMP6 led to robust in vitro cartilage formation from hiMPCs with minimal hypertrophy. Cartilage tissue generated from this new method was resistant to osteogenic transition upon subcutaneous implantation and resulted in a hyaline cartilage‐like regeneration in osteochondral defects in rats. Interestingly, TGFβ3 induced phosphorylation of both Smad2/3 and Smad1/5 in hMSCs, but only activated Smad2/3 in hiMPCs. Supplementing BMP6 activated Smad1/5 and significantly enhanced TGFβ's compacity in inducing hiMPC chondrogenesis. The chondro‐promoting function of BMP6 was abolished by the treatment of a BMP pathway inhibitor. Conclusions: This study describes a robust method to generate chondrocytes from hiMPCs with low hypertrophy for hyaline cartilage repair, as well as elucidates the difference between hMSCs and hiMPCs in response to TGFβ. Our results also indicated the importance of activating both Smad2/3 and Smad1/5 in the initiation of chondrogenesis. Abstract : Activation of Smad1/5 is critical in initiating chondrogenesis of multipotent progenitor cells (iMPCs) created from human induced pluripotent stem cells (iPSCs). iMPCs display rapidly decreased cartilage‐forming capacity with the increase of passage number. When subjected to pellet culture in the medium supplemented with TGFβ3 and BMP6, iMPCs can generate hyaline‐like cartilage with minimal chondrocytic hypertrophy phenotype.